GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG KEPUTIHAN DI POLIKLINIK OBSTETRI/GINEKOLOGI RSU. PANCARAN KASIH GMIM MANADO TAHUN 2014 - Dagasou, Sartje Ellen; Pondaag, Linnie; Lolong, Jill (Universitas Sam Ratulangi, 2014)
Abstrac:Knowledge and good care was a determinant factor in maintaining reproductive health, one of the disorders or diseases of the reproductive organs is vaginal discharge, which is experienced by most women. Whitish or flour albus is the current condition of the vaginal discharge resembling pus or mucus caused by germs. In Indonesia, as many as 75% of women experience vaginal discharge at least once in his life, and 45% of women experience vaginal discharge two or more times in his life. The purpose of this study was to determine the maternal knowledge level overview of whitish in Polyclinic Obstetric/Gynecology in Hospitals ofPancaran Kasih GMIM Manado. This research uses a descriptive research method with a population of 42, with the inclusion criteria with an age range of 20-50 years and 38 samples were taken by means of nonrandom sampling. The results showed the majority of women who visit the clinic Obstetric/Gynecology in Hospitals Pancaran Kasih GMIM Manado have a good level of knowledge. Conclusion to increased outreach efforts and procurement whitish props to push the level of maternal knowledge about the problem of whitish. Keywords : Whitish, knowledge. References : 36 (2003 - 2014), 2 Journal Abstrak, Pengetahuan dan perawatan yang baik merupakan faktor penentu dalam memelihara kesehatan reproduksi, salah satu terjadinya kelainan atau penyakit pada organ reproduksi adalah keputihan, yang dialami oleh sebagian besar wanita.Keputihan atau flour albus adalah kondisi vagina saat mengeluarkan cairan atau lendir yang menyerupai nanah yang disebabkan oleh kuman. Di Indonesia, sebanyak 75 % wanita mengalami keputihan minimal satu kali dalam hidupnya, dan 45 % wanita mengalami dua kali keputihan atau lebih dalam hidupnya. Tujuan penelitian ini adalah mengetahui gambaran tingkat pengetahuan ibu tentang keputihan di Poliklinik Obstetri/Ginekologi RSU Pancaran Kasih GMIM Manado. Jenis penelitian ini menggunakan metode penelitian deskriptif dengan populasi 42, dengan kriteria inklusi dengan rentang usia 20-50 tahun dan diambil sample 38 dengan cara nonrandom sampling. Hasil penelitian menunjukan mayoritas ibu yang berkunjung di Poliklinik Obstetri/Ginekologi RSU Pancaran Kasih GMIM Manado memiliki tingkat pengetahuan baik.Kesimpulan untuk ditingkatkannya upaya penyuluhan keputihan dan pengadaan alat peraga untuk mendorong tingkat pengetahuan ibu tentang masalah keputihan. Kata kunci : Keputihan, pengetahuan. Daftar Pustaka : 36 (2003 – 2014), 2 Jurnal